2019
DOI: 10.1101/604744
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A high-fat diet induces a microbiota-dependent increase in stem cell activity in the Drosophila intestine

Abstract: 18Over-consumption of high-fat diets (HFDs) is associated with several pathologies. Although 19 the intestine is the organ that comes into direct contact with all diet components, the 20 impact of HFD has mostly been studied in organs that are linked to obesity and obesity 21 related disorders. We used Drosophila as a simple model to disentangle the effects of a HFD 22 activation. Surprisingly, we found that a HFD triggered induced stem cell activation 48 critically depends on the indigenous microbiota, as in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…Another pathway pointed out is JAK-STAT signalling pathway, which regulates the transcription of numerous genes and has been implicated in the pathogenesis of several diseases, including inflammatory bowel disease 42 . In addition, it has also been linked to the response of intestinal enterocytes to a high-fat diet, which triggers a transient activation of intestinal stem cells 43 . Historically, in vivo experiments have largely been performed on males to avoid complications related to feminine hormonal cycles, estrous cycle stages, etc., which has led to a sex-biased imbalance in research 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Another pathway pointed out is JAK-STAT signalling pathway, which regulates the transcription of numerous genes and has been implicated in the pathogenesis of several diseases, including inflammatory bowel disease 42 . In addition, it has also been linked to the response of intestinal enterocytes to a high-fat diet, which triggers a transient activation of intestinal stem cells 43 . Historically, in vivo experiments have largely been performed on males to avoid complications related to feminine hormonal cycles, estrous cycle stages, etc., which has led to a sex-biased imbalance in research 44 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that HFD causes a deregulation of the insulin-TOR pathway, at least in the short-term. At the gut level, HFD alters the microbiota, increases intestinal stem cell activity, and increases the number of enteroendocrine cells in the midgut (von Frieling et al, 2020). In this study, it was shown that the HFD directly activates JNK signaling in enterocytes that in turn signal with the cytokine unpaired 3 (upd3) to activate JAK/STAT signaling in the stem cells.…”
Section: Discussionmentioning
confidence: 86%
“…What are the mechanisms behind the shortened lifespan and behavioral senescence in flies kept on HFD? An excess of dietary lipids affects several tissues such as the intestine, the fat body, the central nervous system, and the heart, but also results in global effects on metabolism and the expression of a multitude of genes (Birse et al, 2010;Huang et al, 2020;Jung et al, 2018;Musselman and Kühnlein, 2018;Rivera et al, 2019;von Frieling et al, 2020;Woodcock et al, 2015). Some effects of HFD seem to be tissue specific, others are more global.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations